Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:• The impact of digitizing healthcare services on hospital performance in the Kingdom of Saudi ArabiaDr. Samiyah Rafan Althaqafy, Dr. Mohammad Abdullah Barnawy ,Mr. Faris Omar Batawi• The Role of Explainable Artificial Intelligence (XAI) in Supporting Knowledge Management (KM) and Its Processes: An Analytical StudyMs. Mashael Abdulrahman Al-Hazmi, Ms. Enas Mohammed Al-Najjar, Ms. Wafa Mohna Al-Shaikh• The Impact of Humble Leadership on Enhancing Organizational Commitment "A Field Study of Employees in the Emirate of Jazan Region"Mr. Laghabi Mohammed Yahya, Prof. Alariki, Baseim Qaid• The Impact of Flexible Work Environment on Employee Productivity: A Survey Study at Zain Iraq Telecommunications CompanyLecturer \ Asrar Abdulzahra Ali• The Impact of War Conditions on Multidimensional Poverty and Development in Northwestern Syria: A Field Study of Idlib and Aleppo Governorates in 2024Mr. Ayaz Shukri Taher, Prof. Samir Al-Chikh Ali• The Impact of Using the Balanced Scorecard in Enhancing Organizational Agility: An Applied Study on Technical Colleges in the Asir RegionMs. Raghad Ali Mohammed ,Prof. Mohsen Al-Dabbabi• The Size and Contribution of the Informal Economy in Jordan during the Period 2019-2023Dr. Jihad Ahmad Abu Al-Sondos• Forensic Accounting before the Libyan Judiciary as a Mechanism to Reduce Financial Corruption: A Field Analytical StudyMs. Fathya Gebril Shaitir ,Prof. Jazia Gebril Shaitir
Keywords: Journal of Economic, Administrative and Legal Sciences